THE DEVELOPMENT OF A HUMAN CAPITAL MEASUREMENT AND DISCLOSURE RESEARCH INSTRUMENT FOR THE ZIMBABWEAN MINING COMPANIES - Queen MPOFU; Daniel P. SCHUTTE (Studia Universitatis Babeş-Bolyai Negotia, 2023)
Purpose: The aim of this study is to develop a research instrument to measure and disclose human capital value in the financial statements. The study has been motivated by a lack of guidelines that determine key aspects of human capital despite its contribution to value creation and financial performance. Methodology: This study adopted a post-positivist research philosophy which endorses a quantitative research approach. Quantitative data were collected using the survey questionnaire instrument from the six listed mining companies in Zimbabwe. A convenience sampling technique was utilised and a human capital measurement and disclosure instrument was validated using the exploratory factor analysis. Findings: The paper established eight factors namely; human capital measurements, profitability measures, employee competencies, value drivers, performance-related factors, market-related factors, employee exposures and structure-related factors. The developed questionnaire instrument can be of use to other scholars and policymakers if their studies are aiming to investigate the respondents’ perceptions towards human capital reporting. This will also, provide a basis for the development of a standardised universal approach to measuring human capital value.